Phenomenological Theory of Ion Solvation by Viscosity Studies - Madhurambal, G. (Asian Journal of Chemistry, 2010)
The relative viscosities of the uni-univalent, uni-bivalent, bi-univalent and bi-bivalent electrolytes KCl, Na2SO4, MgCl2, ZnSO4 in different solvent mixtures (20, 40 and 60% benzene-water) with varying concentrations of the salts at temperatures 30º and 35ºC have been determined. The data has been analysed using Jones-Dole equation and Bresleu-Miller equation. The β coefficient values are found to be positive and so the salts can be considered as structure-makers in the solvent mixture. The particle interaction constant and the effective flow volume for all the electrolytes are calculated by the application of Bresleu-Miller equation.